Severe Retinopathy of Prematurity Associated With Neurodevelopmental Disorder in Children - Choi, Young-Jin; Hong, Eun Hee; Shin, Yong Un; Bae, Gi Hwan; Kim, Inah; Cho, Heeyoon (Frontiers in Pediatrics, 2022)
Objective: This study aimed to investigate whether severe retinopathy of prematurity (ROP) could be an association factor for neurodevelopmental disorders in premature infants without other risk factors—such as congenital anomalies, birth injuries, and neurological diseases—that may cause developmental delay. Methods: We used health claims data recorded between 2007 and 2018 in the Korean National Health Insurance Service (KNHIS) database. We recruited a total of 18,256 premature infant born between 2007 and 2008 without congenital anomaly or birth injury (with ROP 6,995, without ROP 11,261) and divided them into four groups as follows: Group A, 209 extremely premature infants (gestational age [GA] <28) with mild ROP; Group B, 75 extremely premature infants (GA <28) with severe ROP; Group C, 6510 other premature infants (28 ≤ GA <37)with mild ROP; and Group D, 201 other premature infants(28 ≤ GA <37) with severe ROP. Using regression analysis, we analyzed whether there was a correlation between ROP prevalence, severity, and developmental delay in premature infants without other risk factors. Results: The prevalence of developmental delay, according to GA and ROP severity, was higher in patients with severe ROP than in the other patients. The prevalence gradually decreased after birth. Among extremely premature infants with ROP, those with severe ROP had a 3.082-fold higher association with neurodevelopmental complications than those with mild ROP (p<0.001). Compared with other premature infants with ROP, those with severe ROP had a 3.269-fold higher association with neurodevelopmental complications than those with mild ROP Conclusion: The severity of ROP may be associated with neurodevelopmental disorders in premature infants.